Solid electrolyte, solid electrolyte layer, and solid electrolyte battery
By designing a solid electrolyte composed of specific elements, the problem of difficulty in improving the ionic conductivity of halide-based solid electrolytes in the existing technology is solved, and a solid electrolyte with high ionic conductivity is achieved, which is suitable for improving the performance of solid electrolyte batteries.
Patent Information
- Application Number
- CN202380026907.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-11
- Filing Date
- 2023-03-13
- Publication Date
- 2025-01-21
AI Technical Summary
Although the ion conductivity of the conventional halide-based solid electrolyte is high, it is subject to various limitations, making it difficult to further improve in the same structure.
By designing a solid electrolyte containing a specific element composition, such as LiaAbEc(SO4)dJeXfHh, to ensure that it has specific peaks in X-ray diffraction and photoelectron spectroscopy measurements, its ion conductivity can be improved.
The ionic conductivity of the solid electrolyte has been improved, ensuring that its ionic conductivity at 25°C reaches above 1mS/cm.
Smart Images

Figure CN119343729A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solid electrolyte, a solid electrolyte layer and a solid electrolyte battery.
[0002] This application claims priority based on Japanese Patent Application No. 2022-038447 filed in Japan on March 11, 2022, and the contents are incorporated herein by reference. Background Art
[0003] In recent years, electronic technology has developed rapidly, achieving small, light, thin and multifunctional portable electronic devices. As a result, for batteries that become power sources for electronic devices, there is a strong desire for small, light, thin and improved reliability, and solid electrolyte batteries using solid electrolytes as electrolytes have attracted much attention. As solid electrolytes, oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes, halide-based solid electrolytes, etc. are known.
[0004] For example, Non-Patent Document 1 states that the ion conductivity of Li3ScCl6 as a halide solid electrolyte is 3 mS / cm, and the potential window on the reduction side is 0.91 V (V vs. Li / Li + ).
[0005] Prior art literature
[0006] Non-patent literature
[0007] Non-patent literature 1: Jianwen Liang et al., Journal of American Chemical Society 2020, 142, 7012-7022. Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] It is said that the ion conductivity of halide solid electrolytes is higher than that of oxide solid electrolytes, sulfide solid electrolytes, complex hydride solid electrolytes, etc. The ion conductivity (3mS / cm) of Li3ScCl6 recorded in Non-Patent Document 1 is high, but it is subject to various restrictions, and sometimes the characteristics recorded in Non-Patent Document 1 cannot be directly reflected or other substances have to be selected. Therefore, in solid electrolytes of the same structure, a structure that can relatively improve ion conductivity is sought.
[0010] The present invention has been developed in view of the above-mentioned problems, and an object of the present invention is to provide a solid electrolyte, a solid electrolyte layer, and a solid electrolyte battery capable of improving ion conductivity.
[0011] Solutions for solving technical problems
[0012] In order to solve the above technical problems, the following solutions are provided.
[0013] (1) The solid electrolyte according to the first embodiment contains Li a A b E c (SO4) d J e X f H h …
[0014] (1). In formula (1), A is at least one element selected from alkali metals and alkaline earth metals other than Li, E is at least one element selected from Al, Ga, In, Sc, Y, Ti, Zr, Hf, and lanthanide elements, and J is at least one element selected from OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3、PO4、P2O7、P3O 10 , SO3, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO, OOC-CH=CH-COO, C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, at least one group selected from O, and X is at least one element selected from F, Cl, Br, and I. In addition, formula (1) satisfies 0.5≤a<6, 0≤b<6, 0<c<2, 0.1<d≤6.0, 0<e≤6.0, 0<f≤6.1, 0≤h≤0.2. In addition, in the solid electrolyte of the first embodiment, in the X-ray diffraction pattern using Cu-Kα as the ray source, a peak is confirmed at a diffraction angle of 2θ=22.3°±1.0°.
[0015] (2) In the solid electrolyte of the above embodiment, a peak can be confirmed at a diffraction angle of 2θ=36.4°±1.0° in an X-ray diffraction pattern using Cu—Kα as a radiation source.
[0016] (3) In the solid electrolyte of the above aspect, peaks can be confirmed at 170±0.5 eV and 532±0.5 eV in X-ray photoelectron spectroscopy.
[0017] (4) In the solid electrolyte of the above aspect, the ion conductivity at 25° C. may be 1 mS / cm or more.
[0018] (5) A solid electrolyte layer according to a second aspect includes the solid electrolyte of the above aspect.
[0019] (6) A solid electrolyte battery according to a third aspect comprises a negative electrode, a positive electrode, and a solid electrolyte layer located between the negative electrode and the positive electrode and containing a solid electrolyte. At least one of the negative electrode, the positive electrode, and the solid electrolyte layer contains the solid electrolyte of the above aspect.
[0020] (7) A solid electrolyte battery according to a fourth aspect includes a negative electrode, a positive electrode, and the solid electrolyte layer of the above aspect located between the negative electrode and the positive electrode.
[0021] Effects of the Invention
[0022] The solid electrolyte of the above aspect can improve ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the X-ray diffraction result of the solid electrolyte according to the present embodiment.
[0024] Figure 2 This is the X-ray diffraction result of the solid electrolyte containing the compound of formula (1).
[0025] Figure 3A This is a diagram showing an enlarged range of the peak originating from O1s in the graph showing the results of X-ray photoelectron spectroscopy measurement of the solid electrolyte according to the present embodiment.
[0026] Figure 3B This is a diagram showing an enlarged range of the peak originating from S2p in the graph showing the results of X-ray photoelectron spectroscopy measurement of the solid electrolyte according to the present embodiment.
[0027] Figure 4 1 is a schematic cross-sectional view of a solid electrolyte battery 100 according to the present embodiment.
[0028] Figure 5 The X-ray diffraction results of Comparative Example 4 are shown.
[0029] Figure 6 3 and 4 are charge and discharge curves of Example 4 and Comparative Examples 3 and 4. DETAILED DESCRIPTION
[0030] Below, with appropriate reference Figure 1 The present embodiment is described in detail. In order to facilitate the understanding of the features of the present invention, the drawings used in the following description sometimes enlarge the features for convenience, and sometimes the dimensional ratios of the components are different from the actual ones. The materials, dimensions, etc. illustrated in the following description are examples, and the present invention is not limited to these, and can be appropriately changed and implemented within the scope of not changing its purpose.
[0031] "Solid Electrolyte"
[0032] A solid electrolyte is a substance that can move ions when an electric field is applied from the outside. If the ion conductivity of the solid electrolyte is high, the transfer of ions in the solid electrolyte battery becomes smooth, and the internal resistance becomes small.
[0033] The solid electrolyte contains Li a A b E c (SO4) d J e X f H h …halide-based solid electrolyte represented by formula (1). The solid electrolyte may contain a material derived from a raw material powder in addition to the compound represented by the above formula (1). The material derived from the raw material powder is, for example, Li2SO4.
[0034] The solid electrolyte may be in the form of a powder (particle) or a sintered body after sintering the powder. In addition, the solid electrolyte may be a molded body formed by compressing the powder; a molded body formed by molding a mixture of powder and a binder; or a coating formed by applying a coating containing powder, a binder, and a solvent and then heating to remove the solvent. In addition, the main structure of the solid electrolyte may be amorphous or crystalline.
[0035] In formula (1), Li is a lithium ion. a satisfies 0.5≤a<6, preferably satisfies 2.0≤a≤4.0, and more preferably satisfies 2.5≤a≤3.5. When E is Zr or Hf, a is preferably 1.0≤a≤3.0, and more preferably 1.5≤a≤2.5. In the compound represented by formula (1), if a is 0.5≤a<6, the content of Li contained in the compound is appropriate, and the ion conductivity of the solid electrolyte layer 10 becomes high.
[0036] In formula (1), A is at least one element selected from alkali metals and alkaline earth metals other than Li. A is replaced by a part of Li ions. A is, for example, Na or Ca. If A is Na or Ca, the potential window on the reduction side of the solid electrolyte becomes wider. b satisfies 0≤b<6. In addition, a+b satisfies 0.5≤a+b<6.
[0037] In formula (1), E is an essential component and is at least one element selected from Al, Ga, In, Sc, Y, Ti, Zr, Hf, and lanthanide elements (La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu). E preferably contains Al, Sc, Y, Zr, Hf, and La, and more preferably contains Zr and Y. E improves the ionic conductivity of the solid electrolyte. c is 0<b<2. In order to more effectively obtain the effect brought about by containing E, c is preferably 0.6≤c. In addition, E is an element that forms the skeleton of the solid electrolyte. c is more preferably c≤1.
[0038] In formula (1), SO4 is sulfate. d satisfies 0.1<d≤6.0, preferably satisfies 0.2≤d≤4.0, and more preferably satisfies 0.4≤d≤2.5. If the solid electrolyte contains sulfate, the potential window on the reduction side of the solid electrolyte becomes wider and is less likely to be reduced.
[0039] In formula (1), J is, for example, selected from OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3、PO4、P2O7、P3O 10 , SO3, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB (bis(oxalatoborate), (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO (succinate), OOC-CH2-COO (malonate), OOC-CH(OH)-CH(OH)-COO (tartrate), OOC-CH( Preferably, J is at least one group selected from OH, SO4, CH3COO, CF3COO, HCOO, and O. J is preferably at least one group selected from OH, SO4, CH3COO, CF3COO, HCOO, and O. J is replaced by a part of sulfate.
[0040] e satisfies 0≤e≤6. In order to make the effect of widening the potential window on the reduction side due to the inclusion of J more significant, e is preferably 0.5≤e. e is preferably e≤3 so as not to cause a decrease in the ion conductivity of the solid electrolyte due to an excessive content of J. In addition, d+e satisfies 0.1<d≤6.0.
[0041] X is at least one selected from F, Cl, Br, and I. In order to improve the ionic conductivity of the solid electrolyte, X is preferably at least one selected from Cl, Br, and I, preferably contains Br and / or I, and particularly preferably contains I. When X contains F, X becomes a solid electrolyte with high ionic conductivity, and therefore, it is preferred to contain F and two or more selected from Cl, Br, and I.
[0042] If X is F, it becomes a solid electrolyte with sufficiently high ion conductivity and excellent oxidation resistance. If X is Cl, it becomes a solid electrolyte with high ion conductivity and a good balance between oxidation resistance and reduction resistance. If X is Br, it becomes a solid electrolyte with sufficiently high ion conductivity and a good balance between oxidation resistance and reduction resistance. If X is I, it becomes a solid electrolyte with high ion conductivity.
[0043] f satisfies 0<f≤6.1. d is preferably 1≤f. If f is 1≤d, when the solid electrolyte is press-formed into a pellet, the strength of the pellet becomes higher. In addition, if f is 1≤f, the ion conductivity of the solid electrolyte becomes higher. In addition, f is preferably f≤5 so that the sulfate is not insufficient due to excessive content of X and the potential window of the solid electrolyte is not narrowed.
[0044] In formula (1), H is hydrogen and h satisfies 0≤h≤0.2.
[0045] The solid electrolyte is, for example, Li2ZrSO4Cl4, Li3YSO4Cl4, Li3ScSO4Cl4, or Li3InSO4Cl4.
[0046] Figure 1 These are the results of X-ray diffraction (XRD) of the solid electrolyte of this embodiment. Figure 1 The vertical axis in the figure is intensity, and the horizontal axis is 2θ. X-ray diffraction was performed using a Cu-α ray source.
[0047] Figure 1 The X-ray diffraction pattern shown is obtained by removing the background data of the polyimide tape from the measurement results. Figure 1 is the X-ray diffraction result of Example 4 described later. Figure 1As shown, the solid electrolyte of this embodiment has a peak at a diffraction angle of 2θ = 22.3° ± 1.0° in the X-ray diffraction pattern using Cu-Kα as the ray source. In addition, the solid electrolyte of this embodiment may also have a peak at a diffraction angle of 2θ = 36.4° ± 1.0° in the X-ray diffraction pattern using Cu-Kα as the ray source.
[0048] These peaks are considered to be derived from Li2SO4, which is a raw material used in the preparation of the compound of formula (1). The peak generated at a diffraction angle 2θ = 22.3° ± 1.0° is the first peak showing the maximum intensity in the X-ray diffraction pattern of Li2SO4.
[0049] The peak generated at the diffraction angle 2θ=36.4°±1.0° is a peak showing a relatively large intensity in the X-ray diffraction pattern of Li 2 SO 4 .
[0050] These peaks disappear when the raw materials are allowed to react sufficiently with each other. Figure 2 This is the X-ray diffraction result of the solid electrolyte containing the compound of formula (1). Figure 2 The X-ray diffraction pattern shown is the raw data of the measurement, and the background data of the polyimide tape has not been removed. The further you go from the front of the paper to the depth, the more the raw materials react with each other. Figure 2 As shown, the peaks generated at the diffraction angle 2θ = 22.3° ± 1.0° and the peaks generated at the diffraction angle 2θ = 36.4° ± 1.0° disappear as the reaction between the raw materials proceeds. Therefore, in the solid electrolyte of this embodiment, it is confirmed that these peaks are part of the unreacted raw material powder (LiSO4) remaining.
[0051] Figure 3A , B is a diagram that enlarges the range of peaks generated in the chart showing the results of X-ray photoelectron spectroscopy measurement of the solid electrolyte of the present embodiment. The solid electrolyte of the present embodiment has peaks at, for example, 170±0.5eV and 532±0.5eV. The peak of 170±0.5eV is a peak of S2p derived from sulfur confirmed in the case of a structure having a bond between sulfur and oxygen, and the peak of 532±0.5eV is a peak of O1s derived from oxygen confirmed in the case of a structure having a bond between sulfur and oxygen. That is, it can be said that there is a portion having a structure of SO4 in the solid electrolyte, and it is believed that the structure originates from unreacted raw material powder (LiSO4).
[0052] As described above, the solid electrolyte of the present embodiment has a specific peak confirmed in X-ray diffraction, and has high ion conductivity. For example, the ion conductivity of the solid electrolyte of the present embodiment is 1 mS / cm or more. The reason why the ion conductivity increases when the solid electrolyte has a specific peak in X-ray diffraction is not clear, but it is believed that this is because the remaining crystalline LiSO4 becomes the starting point for forming a fine structure having a flow path capable of conducting Li ions in the solid electrolyte.
[0053] "Solid electrolyte battery"
[0054] Figure 4 1 is a schematic cross-sectional view of a solid electrolyte battery 100 according to the present embodiment. Figure 4 The solid electrolyte battery 100 shown in the figure includes a power generation element 40 and a package 50. The package 50 covers the periphery of the power generation element 40. The power generation element 40 is connected to the outside via a pair of terminals 60 and 62. Figure 1 In the figure, a stacked battery is shown, but a wound battery may also be used. The solid electrolyte battery 100 is used for, for example, a laminate battery, a square battery, a cylindrical battery, a coin battery, a button battery, and the like.
[0055] <Power generation element>
[0056] The power generation element 40 includes a solid electrolyte layer 10, a positive electrode 20, and a negative electrode 30. The power generation element 40 is charged or discharged by transfer of ions between the positive electrode 20 and the negative electrode 30 via the solid electrolyte layer 10 and transfer of electrons via an external circuit.
[0057] (Solid electrolyte layer)
[0058] The solid electrolyte layer 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The solid electrolyte layer 10 contains a solid electrolyte that can move ions by a voltage applied from the outside. For example, the solid electrolyte conducts lithium ions and inhibits the movement of electrons.
[0059] The solid electrolyte layer 10 is, for example, a halogenide-based solid electrolyte. The solid electrolyte layer 10 contains, for example, the above-mentioned solid electrolyte. When the positive electrode 20 or the negative electrode 30 contains the above-mentioned solid electrolyte, the solid electrolyte contained in the solid electrolyte layer 10 may not be the above-mentioned substance.
[0060] (positive electrode)
[0061] like Figure 4 As shown, the positive electrode 20 includes a plate-shaped (foil-shaped) positive electrode current collector 22 and a positive electrode mixture layer 24. The positive electrode mixture layer 24 is in contact with at least one surface of the positive electrode current collector 22.
[0062] The positive electrode current collector 22 may be made of any electron-conductive material as long as it is resistant to oxidation during charging and is not easily corroded.
[0063] The positive electrode current collector 22 is made of, for example, metal such as aluminum, stainless steel, nickel, titanium, or a conductive resin, etc. The positive electrode current collector 22 may be in the form of a powder, a foil, a pressed product, or an expanded product.
[0064] The positive electrode mixture layer 24 contains a positive electrode active material and, if necessary, contains a solid electrolyte, a binder, and a conductive aid.
[0065] The positive electrode active material is not particularly limited as long as it can reversibly adsorb, release, insert, and desorb (intercalate and deintercalate) lithium ions, and the positive electrode active material used in known solid electrolyte batteries can be used. Examples of the positive electrode active material include lithium-containing metal oxides and lithium-containing metal phosphates.
[0066] Lithium-containing metal oxides include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and lithium nickel oxide (LiNiO2). x Co y Mn z O2 (x + y + z = 1) represented by a composite metal oxide, lithium vanadium compounds (LiVOPO4, Li3V2 (PO4) 3), olivine-type LiMPO4 (wherein M represents at least one selected from Co, Ni, Mn, Fe), lithium titanate (Li4Ti5O 12 )wait.
[0067] In addition, the positive electrode active material may not contain lithium. As such a positive electrode active material, metal oxides (MnO2, V2O5, etc.) that do not contain lithium, metal sulfides (MoS2, etc.) that do not contain lithium, fluorides (FeF3, VF3, etc.) that do not contain lithium, etc. can be cited. When using a positive electrode active material that does not contain lithium, lithium ions are doped into the negative electrode in advance, or a negative electrode containing lithium ions is used.
[0068] The solid electrolyte contained in the positive electrode 20 is, for example, the above-mentioned solid electrolyte. The solid electrolyte contained in the positive electrode 20 may be a halide-based solid electrolyte other than the above-mentioned solid electrolyte.
[0069] The content of the solid electrolyte in the positive electrode mixture layer 24 is not particularly limited, but is preferably 1 to 50% by mass, more preferably 5 to 30% by mass, based on the total mass of the positive electrode active material, solid electrolyte, conductive additive, and binder.
[0070] The binder binds the positive electrode active material, the solid electrolyte, and the conductive additive to each other in the positive electrode mixture layer 24, and firmly bonds the positive electrode mixture layer 24 and the positive electrode collector 22. The positive electrode mixture layer 24 preferably contains a binder. The binder preferably has oxidation resistance and good adhesion.
[0071] As the binder for the positive electrode mixture layer 24, polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymer, metal ion crosslinked body of polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or mixtures thereof, etc. Among them, PVDF is particularly preferably used as the binder.
[0072] The content of the binder in the positive electrode mixture layer 24 is not particularly limited, and is preferably 1% to 15% by mass, more preferably 3% to 5% by mass, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive aid, and the binder. If the amount of the binder is too small, there is a tendency that the positive electrode 20 with sufficient bonding strength cannot be formed. On the contrary, if the amount of the binder is too large, the usual binder is electrochemically inert, and therefore, does not contribute to the discharge capacity, and there is a tendency that it is difficult to obtain sufficient volume or mass energy density.
[0073] The conductive aid improves the electronic conductivity of the positive electrode mixture layer 24. The conductive aid can use a known conductive aid. The conductive aid is, for example, a carbon material such as carbon black, graphite, carbon nanotubes, graphene, a metal such as aluminum, copper, nickel, stainless steel, iron, amorphous metal, a conductive oxide such as ITO, or a mixture thereof. The conductive aid can also be in the form of powder or fiber.
[0074] There is no particular limitation on the content of the conductive aid in the positive electrode mixture layer 24. When a conductive aid is added, the mass ratio of the conductive aid is preferably 0.5 mass % to 20 mass %, more preferably 1 mass % to 5 mass %, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive aid, and the binder.
[0075] (negative electrode)
[0076] like Figure 4 As shown, the negative electrode 30 includes a negative electrode current collector 32 and a negative electrode mixture layer 34 . The negative electrode mixture layer 34 is in contact with the negative electrode current collector 32 .
[0077] The negative electrode current collector 32 only needs to have electron conductivity. The negative electrode current collector 32 is, for example, a metal such as copper, aluminum, nickel, stainless steel, iron, or a conductive resin. The negative electrode current collector 32 may be in the form of a powder, foil, stamped product, or extended product.
[0078] The negative electrode mixture layer 34 contains a negative electrode active material and, if necessary, a solid electrolyte, a binder, and a conductive aid.
[0079] The negative electrode active material is not particularly limited as long as it can reversibly adsorb and release lithium ions, and insert and desorb lithium ions. The negative electrode active material can be any negative electrode active material used in known solid electrolyte batteries.
[0080] The negative electrode active material is a carbon material such as natural graphite, artificial graphite, mesophase carbon microbeads, mesophase carbon fiber (MCF), coke, glassy carbon, organic compound calcined body, Si, SiO x , Sn, aluminum and other metals that can be combined with lithium, their alloys, composite materials of these metals and carbon materials, lithium titanate (Li4Ti5O 12 ), oxides such as SnO2, metallic lithium, etc. The negative electrode active material is preferably natural graphite.
[0081] The solid electrolyte contained in the negative electrode 30 is, for example, the above-mentioned solid electrolyte. The solid electrolyte contained in the negative electrode 30 may be a halogenated solid electrolyte other than the above-mentioned solid electrolyte.
[0082] The binder and the conductive aid contained in the negative electrode 30 are the same as the binder and the conductive aid contained in the positive electrode 20 .
[0083] <Package>
[0084] The package 50 accommodates the power generation element 40 therein. The package 50 prevents moisture and the like from entering the interior from the outside. Figure 4 As shown, the package 50 includes a metal foil 52 and a resin layer 54 laminated on each surface of the metal foil 52. The package 50 is a metal laminate film in which the metal foil 52 is coated with the resin layer 54 from both sides.
[0085] The metal foil 52 is, for example, an aluminum foil or a stainless steel foil. The resin layer 54 can be, for example, a resin film such as polypropylene. The material constituting the resin layer 54 may be different on the inside and outside. For example, as the material on the outside, a high-melting-point polymer such as polyethylene terephthalate (PET) or polyamide (PA) can be used, and as the material on the inside, polyethylene (PE) or polypropylene (PP) can be used.
[0086] <Terminal>
[0087] The terminals 60 and 62 are connected to the positive electrode 20 and the negative electrode 30, respectively. The terminal 60 connected to the positive electrode 20 is a positive terminal, and the terminal 62 connected to the negative electrode 30 is a negative terminal. The terminals 60 and 62 are responsible for electrical connection with the outside. The terminals 60 and 62 are formed of conductive materials such as aluminum, nickel, and copper. The connection method can be welding or threaded fixing. In order to prevent short circuits, the terminals 60 and 62 are preferably protected by insulating tape.
[0088] [Method for manufacturing solid electrolyte battery]
[0089] Next, the manufacturing method of the solid electrolyte battery of the present embodiment is described. First, a solid electrolyte is prepared. For example, raw material powders containing specified elements are mixed at a specified molar ratio, and a solid electrolyte can be manufactured by a mechanochemical reaction method. When the mechanochemical reaction is performed, the unreacted raw material is adjusted in such a way that the unreacted raw material remains in the solid electrolyte. Specifically, by changing the rotation speed, revolution speed, synthesis time, and state of the raw material powder at the time of input of the planetary ball mill, the unreacted components of the raw material can remain.
[0090] In the case where the halide raw material is contained in the raw material powder, the halide raw material is easy to evaporate when the temperature is increased. Therefore, the halogen gas can also be made to coexist in the atmosphere during sintering to supplement the halogen. In addition, in the case where the halide raw material is contained in the raw material powder, it is also possible to sinter by hot pressing using a mold with high airtightness. In this case, the mold has high airtightness, so the evaporation of the halide raw material caused by sintering can be suppressed. By sintering in this way, a solid electrolyte in the state of a sintered body composed of a compound having a specified composition is obtained.
[0091] Next, the positive electrode 20 is prepared. The positive electrode is produced by applying a paste containing a positive electrode active material onto the positive electrode current collector 22 and drying it to form a positive electrode mixture layer 24. The above-mentioned solid electrolyte may be added to the paste containing the positive electrode active material.
[0092] Next, the negative electrode 30 is prepared. The negative electrode is produced by applying a paste containing a negative electrode active material onto the negative electrode current collector 32 and drying it to form a negative electrode mixture layer 34. The above-mentioned solid electrolyte may be added to the paste containing the negative electrode active material.
[0093] The power generation element 40 can be manufactured using a powder molding method, for example. A guide having a hole is provided on the positive electrode 20, and a solid electrolyte is filled into the guide. Then, the surface of the solid electrolyte is flattened, and the negative electrode 30 is overlapped on the solid electrolyte. Thus, the solid electrolyte is sandwiched between the positive electrode 20 and the negative electrode 30. Then, by applying pressure to the positive electrode 20 and the negative electrode 30, the solid electrolyte is press-formed. By press-forming, a laminated body in which the positive electrode 20, the solid electrolyte layer 10, and the negative electrode 30 are sequentially stacked is obtained.
[0094] Next, external terminals are welded to the positive electrode collector 22 of the positive electrode 20 and the negative electrode collector 32 of the negative electrode 30 respectively, and the positive electrode collector 22 or the negative electrode collector 32 is electrically connected to the external terminal by a known method. Then, the laminate connected to the external terminal is housed in the package 50, and the opening of the package 50 is heat-sealed to seal it. Through the above steps, the solid electrolyte battery 100 of this embodiment is obtained.
[0095] Since the solid electrolyte battery 100 of the present embodiment contains the above-mentioned solid electrolyte, the conduction of Li ions is smooth and the internal resistance is low.
[0096] Although the embodiments of the present invention have been described in detail with reference to the drawings, each structure in each embodiment and their combination are merely examples, and addition, omission, replacement, and other changes to the structure may be made without departing from the spirit of the present invention.
[0097] Example
[0098] "Example 1"
[0099] (Preparation of solid electrolyte)
[0100] In a glove box with a dew point of about -75°C, the raw material powders are weighed in a manner such that the molar ratio of zirconium chloride (ZrCl4) and lithium sulfate (Li2SO4) is 1:8. First, the Li2SO4 before mixing is crushed for 1 hour using a planetary ball mill. The rotation speed during crushing is set to 300 rpm. Next, the raw material powder is added to a zirconia sealed container for a planetary ball mill in which zirconia balls are pre-placed. Next, a lid is placed on the sealed container, the lid is screwed onto the container body, and polyimide tape is further used to seal the lid and the container. Polyimide tape has the effect of isolating moisture. Next, the zirconia sealed container is placed on a planetary ball mill. Set the rotation speed to 200 rpm and the revolution speed to 200 rpm, set the rotation direction of the rotation and the revolution direction to opposite directions, mix the raw material powders, and react mechanochemically for 2 hours to generate a solid electrolyte (Li4Zr 0.25 (SO4)2Cl).
[0101] The planetary ball mill is set in a normal atmosphere (air). The zirconia sealed container used in the planetary ball mill is screwed and further sealed with a polyimide tape. When the zirconia sealed container is placed on the planetary ball mill, the zirconia sealed container is firmly pressed and fixed. Therefore, it is believed that even in a normal atmosphere, moisture will hardly mix into the zirconia sealed container from the air.
[0102] [XRD measurement]
[0103] In a glove box with a dew point of about -70°C where argon gas circulates, the prepared solid electrolyte is filled on a holder for XRD measurement. Then, a moisture-proof polyimide tape (polyimide tape dried in vacuum at 70°C for 16 hours) is pasted to cover the filled surface for sealing, and an XRD measurement sample is prepared. Next, it is taken out into the atmosphere and an X-ray diffraction device (X'PertPro manufactured by PANalytical Company) is used for XRD measurement. The X-ray source uses Cu-Kα rays.
[0104] In addition, under the same conditions as the above XRD measurement, only the polyimide tape for moisture protection was attached to the XRD measurement stand to perform background measurement. The X-ray diffraction pattern of the prepared solid electrolyte had peaks at diffraction angles 2θ = 22.3° ± 1.0° and 2θ = 36.4° ± 1.0°.
[0105] [XPS measurement]
[0106] In addition, X-ray photoelectron spectroscopy was also performed. The samples were collected in a glove box with a dew point of about -70°C where argon gas was circulated, and transported to an XPS measuring device without being exposed to the atmosphere. The XPS measurement was performed using Quantera2 manufactured by PHI. As a result, the prepared solid electrolyte confirmed peaks at 170±0.5eV and 532±0.5eV.
[0107] [Measurement of ion conductivity]
[0108] Next, in a glove box with a dew point of about -70°C in which argon gas was circulated, the obtained solid electrolyte powder was filled into a press-molding die and press-molded at a load of about 30 KN to produce a measurement cell for ion conductivity.
[0109] The die for press molding was composed of a PEEK (polyetheretherketone) cylinder with a diameter of 10 mm, and an upper punch and a lower punch made of SKD11 material with a diameter of 9.99 mm.
[0110] Then, a stainless steel disc and a Teflon (trademark registration) disc with a diameter of 50 mm and a thickness of 5 mm having threaded holes at four locations were prepared, and a press-molding die was set as follows. The stainless steel disc / Teflon (trademark registration) disc / press-molding die / Teflon (trademark registration) disc / stainless steel disc were loaded in the order of the four screws tightened with a torque of about 3 N·m. In addition, screws were inserted into the threaded holes provided on the sides of the upper and lower punches, and set as external connection terminals.
[0111] The external connection terminal was connected to a potentiostat (VersaSTAT3 manufactured by Princeton Applied Research Corporation) equipped with a frequency response analyzer, and the ionic conductivity was measured using an impedance measurement method. The measurement was performed at a measurement frequency range of 1 MHz to 0.1 Hz, an amplitude of 10 mV, and a temperature of 25°C. The ionic conductivity of the solid electrolyte of Example 1 was 1.1×10 -3 S / cm.
[0112] "Examples 2 to 8"
[0113] Examples 2 to 8 differ from Example 1 in that the materials and molar ratios of the raw material powders were changed. In Examples 2 to 8, solid electrolyte measurements were performed in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Table 1 below.
[0114] "Examples 9 to 21"
[0115] Examples 9 to 21 differ from Example 1 in that the material and molar ratio of the raw material powders were changed and the production conditions of the solid electrolyte were altered. In Examples 9 to 21, the solid electrolyte was measured in the same manner as in Example 1.
[0116] Examples 9 to 21 are prepared in the following order. First, in a glove box with a dew point of about -75°C, zirconium chloride (ZrCl4), lithium sulfate (Li2SO4), and other raw materials are weighed in a prescribed molar ratio. Next, using a planetary ball mill, the pre-mixed Li2SO4 is crushed at a rotation speed of 300 rpm for 1 hour, and then ZrCl4 is added and further crushed at a rotation speed of 200 rpm for 1 hour. Next, the crushed sample and other raw materials are placed in a zirconia sealed container for a planetary ball mill in which zirconia balls are pre-placed. Then, the rotation speed is set to 200 rpm and the revolution speed is set to 200 rpm, and the rotation direction of the rotation and the revolution direction are set to opposite directions, so that the mechanochemical reaction is carried out for a prescribed time to generate the desired solid electrolyte.
[0117] In Examples 9 to 21, the solid electrolyte was measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Table 1 below.
[0118] "Examples 22 to 25"
[0119] Examples 22 to 25 differ from Example 1 in that the material and molar ratio of the raw material powder were changed and the production conditions of the solid electrolyte were altered. In Examples 22 to 25, the solid electrolyte was measured in the same manner as in Example 1.
[0120] Examples 22 to 25 were prepared in the following order. First, in a glove box with a dew point of about -75°C, Li2O, ZrCl4, and Li2SO4 were weighed in a predetermined molar ratio. First, Li2SO4 was crushed at a rotation speed of 200 rpm for 1 hour before mixing. Next, after mixing Li2O and ZrCl4 at a rotation speed of 300 rpm for 48 hours, Li2SO4 was added and allowed to react mechanochemically for a predetermined time to generate the desired solid electrolyte.
[0121] In Examples 22 to 25, the solid electrolyte was measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Table 2 below.
[0122] "Example 26"
[0123] In Example 26, the material and molar ratio of the raw material powder were changed, and the production conditions of the solid electrolyte were changed, which was different from Example 1. In Example 26, the solid electrolyte was measured in the same manner as in Example 1.
[0124] First, in a glove box with a dew point of about -75°C, Li3PO4, ZrCl4, and Li2SO4 were weighed in a predetermined molar ratio. First, Li2SO4 was crushed at 200 rpm for 1 hour before mixing. Then, Li3PO4 and ZrCl4 were mixed at 300 rpm for 24 hours, and then Li2SO4 was added to react mechanochemically for a predetermined time to generate the desired solid electrolyte.
[0125] In Example 26, the solid electrolyte was measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Table 2 below.
[0126] "Examples 27 to 29"
[0127] Examples 27 to 29 differ from Example 1 in that the material and molar ratio of the raw material powder were changed and the production conditions of the solid electrolyte were altered. In Examples 27 to 29, the solid electrolyte was measured in the same manner as in Example 1.
[0128] First, in a glove box with a dew point of about -75°C, Li2O and LiX were mixed at a molar ratio of 2:1. The mixing was performed using the planetary ball mill described above at a rotation speed of 300 rpm for 48 hours. Next, the LZSOC synthesized in Example 4 was added and the mechanochemical reaction was carried out at a rotation speed of 200 rpm for a predetermined time to generate the desired solid electrolyte.
[0129] In Examples 27 to 29, the solid electrolyte was measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Table 2 below.
[0130] "Examples 30 and 31"
[0131] In Examples 30 and 31, the dew point of the drying chamber during mixing was different from that in Example 4. In Example 30, the dew point was set to -40°C, and in Example 31, the dew point was set to -60°C. The other conditions were the same as in Example 4, and the solid electrolyte was measured. The composition, molar ratio, and measurement results of each raw material are described in Table 2 below.
[0132] "Examples 32-34"
[0133] Examples 32 to 34 differ from Example 1 in that the material and molar ratio of the raw material powder were changed and the production conditions of the solid electrolyte were altered. In Examples 32 to 34, the solid electrolyte was measured in the same manner as in Example 1.
[0134] First, ZrCl4 and LiX were mixed at a predetermined molar ratio in a glove box at a dew point of about -75°C. The mixture was mixed using the planetary ball mill at a rotation speed of 300 rpm for 24 hours. Then, the LZSOC synthesized in Example 4 was added and the mechanochemical reaction was carried out at a rotation speed of 200 rpm for a predetermined time to generate the desired solid electrolyte.
[0135] In Examples 32 to 34, the solid electrolyte was measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Tables 3 and 4 below.
[0136] "Examples 35 to 45"
[0137] Examples 35 to 45 differ from Example 1 in that the material and molar ratio of the raw material powder were changed and the production conditions of the solid electrolyte were altered. In Examples 35 to 45, the solid electrolyte was measured in the same manner as in Example 1.
[0138] First, ZrCl4, LiCl, and LiX were mixed at a predetermined molar ratio in a glove box at a dew point of about -75°C. The mixture was mixed using the planetary ball mill at a rotation speed of 300 rpm for 24 hours. Then, the LZSOC synthesized in Example 4 was added and the mechanochemical reaction was carried out at a rotation speed of 200 rpm for a predetermined time to generate the desired solid electrolyte.
[0139] In Examples 35 to 45, the solid electrolyte was measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Tables 3 and 4 below.
[0140] "Comparative Examples 1 to 11"
[0141] Comparative Examples 1 to 11 differ from Example 1 in that the material and molar ratio of the raw material powders were changed and the production conditions of the solid electrolyte were altered. In Comparative Examples 1 to 11, the solid electrolyte was measured in the same manner as in Example 1.
[0142] In the solid electrolyte manufacturing methods of Comparative Examples 1 to 11, the rotation speed of the planetary ball mill during the mechanochemical reaction is set to 300 rpm, the revolution speed is set to 300 rpm, and Li2SO4 is not crushed before mixing but used. This point and the reaction time of the mechanochemical reaction (mixing time of the raw material powder) are different from the solid electrolyte manufacturing method of Example 1.
[0143] In Comparative Examples 1 to 11, the solid electrolyte was measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are shown in Table 2 below. Figure 5 ] The X-ray diffraction results of Comparative Example 4 are shown. In Comparative Example 4, no peaks were confirmed at diffraction angles 2θ = 22.3° ± 1.0° and 2θ = 36.4° ± 1.0°. Figure 5 The X-ray diffraction pattern shown is a pattern obtained by removing the background data of the polyimide tape from the measurement results.
[0144] "Comparative Example 12"
[0145] In Comparative Example 12, the dew point of the drying chamber during mixing was different from that in Example 4. In Comparative Example 12, the dew point was set to -20°C. The other conditions were the same as in Example 4, and the solid electrolyte was measured. The composition, molar ratio, and measurement results of each raw material are shown in Table 2 below.
[0146] [Table 1]
[0147]
[0148] [Table 2]
[0149]
[0150] [Table 3]
[0151]
[0152] [Table 4]
[0153]
[0154] In Tables 1 and 2 above, LZOC is a mixture of Li2O and ZrCl4. LZSOC is a mixture of Li2SO4 and ZrCl4. LZPOC is a mixture of Li3PO4 and ZrCl4. In addition, "A" in the XRD column indicates that a peak is confirmed, and "B" indicates that a peak is not confirmed. In the XPS analysis, peaks are confirmed at 170±0.5 eV and 532±0.5 eV in any of the Examples and Comparative Examples.
[0155] (Fabrication of all-solid-state batteries)
[0156] All-solid batteries are also made in a glove box with a dew point of about -70°C. All-solid batteries are made using a pellet making jig. The pellet making jig has a PEEK (polyetheretherketone) bracket with an inner diameter of 10mm, and an upper punch and a lower punch with a diameter of 9.99mm. The upper and lower punches are made of die steel (SKD11 material).
[0157] The lower punch was inserted into the PEEK holder of the pellet making jig, and 50 mg of solid electrolyte was placed on the lower punch. Next, the resin holder was vibrated to make the surface of the solid electrolyte uniform, and then the upper punch was inserted on the solid electrolyte, and a punching machine was used to press with a weight of about 4 KN.
[0158] Next, the lower punch was pulled out, and 10 mg of the negative electrode mixture was placed on the solid electrolyte. Next, the PEEK bracket was vibrated to make the surface of the negative electrode mixture uniform, and the lower punch was inserted into the negative electrode mixture, and a punch was used to press with a weight of 3KN. The negative electrode mixture is composed of a negative electrode active material and the above-mentioned solid electrolyte, and the negative electrode active material uses lithium titanate (LTО) with an average particle size of 6.0μm. Next, the upper punch was pulled out, and 10 mg of the positive electrode mixture was placed on the solid electrolyte layer. Next, the PEEK bracket was vibrated to make the surface of the positive electrode mixture uniform, and the upper punch was inserted into the positive electrode mixture, and a punch was used to press with a weight of 3KN. The positive electrode mixture is composed of a positive electrode active material, carbon as a conductive additive, and the above-mentioned solid electrolyte, and the positive electrode active material uses lithium cobalt oxide (LCО) with an average particle size of 7.5μm. In this way, a fully solid-state battery was produced in which the negative electrode mixture layer, the solid electrolyte layer, and the positive electrode mixture layer were stacked in this order.
[0159] In addition, two stainless steel plates with a diameter of 50 mm and a thickness of 5 mm and two Bakelite (registered trademark) plates with a diameter of 50 mm and a thickness of 2 mm were prepared. Next, four holes for screws to pass through were respectively provided on the two stainless steel plates and the two Bakelite (registered trademark) plates. The holes for screws to pass through were provided at a position where the two stainless steel plates and the two Bakelite (registered trademark) plates overlapped when viewed from above when the electrochemical cell, the two stainless steel plates, and the two Bakelite (registered trademark) plates were stacked, and did not overlap with the electrochemical cell when viewed from above.
[0160] Then, the stainless steel plate, bakelite (registered trademark) plate, all-solid battery, bakelite (registered trademark) plate, and stainless steel plate are stacked in sequence, screws are inserted into the above-mentioned threaded holes, and tightened with a torque of 1N·m. In this way, an all-solid battery in which the upper and lower punches of the electrochemical cell are insulated by the bakelite (registered trademark) plate is obtained. Next, the all-solid battery is left to stand in a constant temperature bath at 25°C for 48 hours to stabilize the open circuit voltage.
[0161] The rate characteristics are evaluated using the manufactured all-solid-state battery. The rate characteristics are evaluated based on the ratio of the discharge capacitance when discharged at a discharge rate of 1C to the discharge capacitance at a discharge rate of 0.1C (1C / 0.1C rate characteristics). The all-solid-state battery is subjected to constant current charging (CC charging) at a constant current rate of 0.1C at 25°C until the battery voltage reaches 2.7V. After reaching 2.7V, it is charged (CV charging) until the current becomes equivalent to 0.05C. Then, it is discharged (CC discharge) at a constant current rate of 0.1C until the battery voltage reaches 1.5V, and the discharge capacitance at 0.1C is measured. Next, the all-solid-state battery is charged again under the above conditions, discharged at a discharge rate of 1C until the battery voltage reaches 1.5V, and the discharge capacitance at 1C is measured. The measurement results are also summarized in Tables 1, 2, 3, and 4.
[0162] in addition, Figure 6 : are the charge and discharge curves of Example 4 and Comparative Examples 3 and 4. Example 4 is represented by a dotted line, Comparative Example 3 is represented by a dotted line, and Comparative Example 4 is represented by a solid line. Figure 6 As shown, Example 4 confirmed higher input-output characteristics than Comparative Examples 3 and 4.
[0163] Industrial Applicability
[0164] According to the present invention, a solid electrolyte having improved ion conductivity can be obtained.
[0165] Explanation of symbols
[0166] 10Solid electrolyte layer
[0167] 20 positive electrode
[0168] 22Positive electrode collector
[0169] 24 positive electrode mixture layer
[0170] 30 negative electrode
[0171] 32 Negative electrode collector
[0172] 34 Negative electrode mixture layer
[0173] 40 Power generation elements
[0174] 50 Package
[0175] 52 metal foil
[0176] 54 resin layer
[0177] 60, 62 terminals
[0178] 100 solid electrolyte battery
Claims
1. A solid electrolyte, wherein: Contains Li a A b E c (SO4) d J e X f H h …(1) In formula (1), A is at least one element selected from alkali metals and alkaline earth metals other than Li, E is at least one element selected from Al, Ga, In, Sc, Y, Ti, Zr, Hf, and lanthanide elements, J is selected from OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3、PO4、P2O7、P3O 10 , SO3, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO, OOC-CH=CH-COO, C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, at least one group selected from the group consisting of O, X is at least one element selected from F, Cl, Br, and I, Satisfying 0.5≤a<6, 0≤b<6, 0<c<2, 0.1<d≤6.0, 0<e≤6.0, 0<f≤6.1, 0≤h≤0.2, In the X-ray diffraction pattern using Cu—Kα as a radiation source, a peak was confirmed at a diffraction angle of 2θ=22.3°±1.0°.
2. The solid electrolyte according to claim 1, wherein In the X-ray diffraction pattern using Cu—Kα as a radiation source, a peak was confirmed at a diffraction angle of 2θ=36.4°±1.0°.
3. The solid electrolyte according to claim 1 or 2, wherein In X-ray photoelectron spectroscopy measurement, peaks were confirmed at 170±0.5 eV and 532±0.5 eV.
4. The solid electrolyte according to any one of claims 1 to 3, wherein The ion conductivity at 25°C is 1 mS / cm or more.
5. A solid electrolyte layer, wherein: Contains the solid electrolyte according to any one of claims 1 to 4.
6. A solid electrolyte battery, wherein: A negative electrode, a positive electrode, and a solid electrolyte layer located between the negative electrode and the positive electrode and containing a solid electrolyte. At least one of the negative electrode, the positive electrode, and the solid electrolyte layer contains the solid electrolyte according to any one of claims 1 to 4.
7. A solid electrolyte battery, wherein: A device comprising a negative electrode, a positive electrode, and the solid electrolyte layer according to claim 5 located between the negative electrode and the positive electrode.
Citation Information
Patent Citations
Vehicle
JP2022038447A
Cited By
Polyanion solid electrolyte, preparation method thereof and solid-state battery
CN119560625A
A polyanion solid electrolyte and its preparation method and solid-state battery
CN119560625B
Heteroanion oxyhalide solid electrolyte, preparation method and application thereof, and all-solid-state battery
CN121484182A